2022
DOI: 10.1111/jcpt.13711
|View full text |Cite
|
Sign up to set email alerts
|

The population pharmacokinetics and dose optimization of polymyxin B in critically ill patients with or without extracorporeal membrane oxygenation

Abstract: What is known and objective: The presence of extracorporeal membrane oxygenation (ECMO) is suggested to further exacerbate the pharmacokinetics (PK) alterations that occur during critical illness. The objectives of this study were to determine the population PK model of polymyxin B in critically ill patients with or without ECMO support investigated the influence of ECMO on PK variability and to identify an optimal dosing strategy.Methods: Forty-four critically ill patients were enrolled, including eight patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…Interestingly, a higher proportion of patients reached the ssAUC 0-24 standard of 50–100 mg ·h/L in the septic shock subgroup compared to the total group. Hence, we compared some baseline characteristics between sepsis patients with and without shock to explain why target AUC compliance rates were high in more severe patients, and the results showed that the level of Scr was significantly higher in patients with septic shock and the plasma concentration of polymyxin B appeared to increase with increasing Scr; a similar phenomenon was described in previous studies [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, a higher proportion of patients reached the ssAUC 0-24 standard of 50–100 mg ·h/L in the septic shock subgroup compared to the total group. Hence, we compared some baseline characteristics between sepsis patients with and without shock to explain why target AUC compliance rates were high in more severe patients, and the results showed that the level of Scr was significantly higher in patients with septic shock and the plasma concentration of polymyxin B appeared to increase with increasing Scr; a similar phenomenon was described in previous studies [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 59%